2012
DOI: 10.1007/s00244-012-9789-9
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Application and Detection in Variable Agricultural Intensity Watersheds and Their River Systems in the Maritime Region of Canada

Abstract: Applications of pesticides in areas of agricultural production have been an environmental concern for the past several decades. Varying-sized watersheds draining regions of intense agriculture in the Maritime Provinces of Canada were monitored between 2003 and 2007 to determine the major in-use pesticides and to gain an understanding of the risks posed to aquatic ecosystems. A questionnaire collected from farmers in one watershed intensively cropped with potato indicated that 43 pesticides were applied with 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Studies were performed at the catchment scale in temperate conditions to better understand the effects of hydrology, pesticide application rates, land uses, and molecular characteristics on the water contamination by pesticides (Blanchard and Lerch, 2000;Guo et al, 2004;Leu et al, 2004;Lewis et al, 2016). Studies focused on water pollution resulting either from pesticides used in agriculture (Palma et al, 2004;Wightwick et al, 2012;Xing et al, 2012) or in urban area (Blanchoud et al, 2004). In the tropical context, several research has been conducted on water contamination by pesticides (Lewis et al, 2016), but few were conducted in tropical context at the catchment scale (Houdart et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies were performed at the catchment scale in temperate conditions to better understand the effects of hydrology, pesticide application rates, land uses, and molecular characteristics on the water contamination by pesticides (Blanchard and Lerch, 2000;Guo et al, 2004;Leu et al, 2004;Lewis et al, 2016). Studies focused on water pollution resulting either from pesticides used in agriculture (Palma et al, 2004;Wightwick et al, 2012;Xing et al, 2012) or in urban area (Blanchoud et al, 2004). In the tropical context, several research has been conducted on water contamination by pesticides (Lewis et al, 2016), but few were conducted in tropical context at the catchment scale (Houdart et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is found in soils and in the atmosphere, making drift issues a major environmental problem (Weber et al, 2010;White et al, 2006). Endosulfan was detected in freshwater streams in about 6% of the samples in 1-4 years over a 5-year period (2003-2007) in intensive potato production regions of PEI (Xing et al, 2012). Maximum endosulfan concentration in freshwater streams for PEI was about 10 µg•L -1 with a highest annual mean of 0.64 µg•L -1 which exceed endosulfan concentrations recommended by the Canadian Water Quality Guidelines for the protection of aquatic life (CCME, 2010), which is 0.09 µg•L -1 for a short-term exposure in marine water or 0.06 µg•L -1 for freshwater.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned process induces changes in the chemical composition of the water, subsequently influencing the organisms inhabiting the area [5]. Previous studies have indicated that herbicides can have adverse effects on fish, such as reduced reproduction, alterations in behavior, loss of biodiversity, and genetic, neurological, and hemato-immunological disorders [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%